Gas Adsorption of Carbon Nanotubes: Tube-Molecule Interaction and Technological Applications - Zhao, Jijun (Current Nanoscience, 2005)
In this review, we summarize the current progress in the gas adsorptions of carbon nanotubes. Experimentally, the electronic and transport properties of carbon nanotubes are found to be sensitive to the adsorption of gaseous molecules. From first principle calculations, most molecules (e.g. NH3, N2, CO2, CH4, H2O, Ar, C6H6 and C6H12, etc.) adsorb weakly on nanotubes and act as charge donors to the nanotubes. With adsorption of some acceptor molecules such as NO2, O2 and C8N2O2Cl2 (DDQ), the hybridization between nanotube and molecules substantially affects the electronic and transport properties of SWNTs. Hence, gas adsorption on nanotube has significant effect on the field emission properties and might lead to new opportunities in chemical sensors.
Keywords: nanoelectronic devices